О некоторых свойствах и оценках для последовательностей простых чисел - Ивохин, Е.В.; Ваднев, Д.А. (Проблемы управления и информатики, 2015)
Розглянуто спеціальні послідовності простих чисел, їх властивості, введено операції на розглянутих послідовностях, отримано оцінки для інтервалів розміщення найближчих до заданого числа простих чисел. Запропоновано алгоритм для наближення довільного раціонального числа за допомогою елементів введених послідовностей простих чисел. Доведено твердження для оцінок інтервалів розміщення найближчих до заданого цілого простих чисел. Отримані результати дозволяють обгрунтувати методику побудови трикутних нечітких чисел у вигляді інтервалів, границі яких обираються за допомогою елементів спеціальних послідовностей простих чисел. The specific sequences of prime numbers, their properties, operations introduced on these sequences are considered. The estimates for arrangement intervals of the prime numbers the closest to the specified number are obtained. An algorithm to approximate an arbitrary rational number using elements of introduced sequences of primes is proposed. The statement for estimates of arrangement intervals of the closest to specified integer prime numbers. are proved. The obtained results enable us to substantiate the method of constructing triangular fuzzy numbers in the form of intervals the boundaries of which are selected using the members ofspecial sequences of prime numbers.